Language interaction in the english teaching learning process through ecuadorian traditional games in the students at Domingo Faustino Sarmiento school during the academic cycle april-august 2015 - Banda Muñoz, Carmen Gabriela (2015)
The present research consists to improve the English learning through Ecuadorian Traditional Games in the students at Domingo Faustino Sarmiento School during the period 20014-1015; due to the lack of interest and motivation in students at the moment to learn this language; that’s why it can be determined the necessity to expand it.Moreover, it was determined the decree use of didactic activities in the English Teaching learning process, that’s why the importance to solve it through this investigative work which has been developed and based on the socio-educative, theoretical, didactic and meaningful mode; where the proposal contains different Ecuadorian traditional games in order to motivate students, increase their interest in the English learning and at the same time children can work in an confidence environment so as develop their abilities….